Crossing religious boundaries Islam, Christianity and 'Yoruba religion' in Lagos, Nigeria - Janson, Marloes 1973- (The International African Library, 2021)
Religious pluralism, as encountered in multi-faith settings such as Nigeria's biggest city Lagos, challenges much of what we have long taken for granted about religion, including the ready-made binaries of Christianity versus Islam, religion versus secularism, religious monism versus polytheism, and tradition versus modernity. In this book, Marloes Janson offers a rich ethnography of religions, religious pluralism and practice in Lagos, analysing how so-called 'religious shoppers' cross religious boundaries, and the coexistence of different religious traditions where practitioners engage with these simultaneously. Prompted to develop a broader conception of religion that shifts from a narrow analysis of religious traditions as mutually exclusive, Janson instead offers a perspective that focuses on the complex dynamics of their actual entanglements. Including real-life examples to illustrate religion in Lagos through religious practice and lived experiences, this study takes account of the ambivalence, inconsistency and unpredictability of lived religion, proposing assemblage as an analytical frame for exploring the conceptual and methodological possibilities that may open as a resu